Nepal between dragon and elephant - Timalsina, Saroj Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Nepal, a landlocked country surrounded by mountains, enjoys the strategic advantage of being sandwiched between two rising global powers—the Elephant (India) and the Dragon (China). There is opportunity as well as danger. Nepal benefits from improved connectivity, border trade, foreign investment, and infrastructure support because to China's Belt and Road Initiative (BRI) and India's development partnership. Because of its closeness to two of the world's largest markets, Nepal has the potential to serve as a transit hub, fostering regional integration and economic diversification. However, historical weaknesses, economic exposure, and geopoliticalcompetition also present Nepal with a wide range of challenges. Nepal's dependence on India for its transit route and commercial corridor, as well as boundary disputes with both of its neighbors, limit its strategic autonomy. However, expanding Chinese involvement and offering options could force Nepal into a great power struggle, which is risky. Such actions further jeopardize Nepal'ssovereignty and national political equilibrium. Nepal has adopted an equidistant diplomacy strategy, which leverages its geopolitical location to create developmental gains without resorting to overt alignment to maneuver in this difficult situation. Nepal strives to turn its geopolitical factors into advantages by emphasizing regionalism, multilateralism, and non-alignment. Nepal needs improve its infrastructure, diversify its trade, foster good governance, and bolster its internal capabilities in order to ensure sustainable national progress. Last but not least, Nepal's success is a result of its ability to protect its sovereignty and advance inclusive development whilebalancing the competing interests of its neighbors through a dance-like orchestration of tactics. Its "in-between Dragon and Elephant" status is therefore both advantageous and a test of its future direction.